2021
DOI: 10.1021/acs.est.1c03617
|View full text |Cite
|
Sign up to set email alerts
|

SO2 Poisoning Mechanism of the Multi-active Center Catalyst for Chlorobenzene and NOx Synergistic Degradation at Dry and Humid Environments

Abstract: The performance of fresh (PdV/TiO 2 ), sulfur poisoned (Used-S and Used-H), and regenerated (Used-R S and Used-R H ) multi-active center catalysts for chlorobenzene catalytic oxidation and selective catalytic reduction (CBCO + SCR) reaction is investigated. The reaction on the catalyst surface is blocked after sulfur poisoning owing to the occupation and deposition of catalyst active centers (mainly Pd centers) by PdSO 4 (and/or PdS in a dry environment) and NH 4 HSO 4 species, especially the CBCO process. Sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…As for Cu 2p spectra (Figure S2b), CuMn-II obviously exhibits a more balanced distribution of Cu + and Cu 2+ , which is favorable for the electron replenishment to generate more active oxygen species . Significantly, CuMn-II shows excellent acidity, and three peaks at 161, 332, and 618 °C emerge in the NH 3 -TPD profiles, suggesting the coexistence of weak, moderate, and strong acidity (Figure g) . In comparison, CuMn-I only possesses weak acidity at 153 °C.…”
Section: Results and Disccusionmentioning
confidence: 91%
See 1 more Smart Citation
“…As for Cu 2p spectra (Figure S2b), CuMn-II obviously exhibits a more balanced distribution of Cu + and Cu 2+ , which is favorable for the electron replenishment to generate more active oxygen species . Significantly, CuMn-II shows excellent acidity, and three peaks at 161, 332, and 618 °C emerge in the NH 3 -TPD profiles, suggesting the coexistence of weak, moderate, and strong acidity (Figure g) . In comparison, CuMn-I only possesses weak acidity at 153 °C.…”
Section: Results and Disccusionmentioning
confidence: 91%
“…39 Significantly, CuMn-II shows excellent acidity, and three peaks at 161, 332, and 618 °C emerge in the NH 3 -TPD profiles, suggesting the coexistence of weak, moderate, and strong acidity (Figure 1g). 40 In comparison, CuMn-I only possesses weak acidity at 153 °C. CuMn-II exhibits superiority in the NH 3 desorption amount compared to CuMn-I, ca.…”
Section: Characterization Of Catalystsmentioning
confidence: 99%
“…However, the complex components ( e.g. , As, Pb, SO 2 , H 2 O) in the flue gases of industrial processes often result in mutual interferences in the MPC reaction, which thereby complicates the MPC performance of the V 2 O 5 –WO 3 /TiO 2 catalyst. , Over the years, studies on the resistance to interferences in the NH 3 -SCR process have been extensively explored. However, few studies have investigated the MPC interference mechanism and anti-interference. , Our previous work demonstrated that the loaded As 2 O 3 species distinctly decreased the oxygen vacancy formation energy at the V–O–V site, which likely contributed to the extensive formation of more toxic polychlorinated byproducts in the MPC reaction. Moreover, the As 2 O 5 species vigorously attacked the neighboring VO sites, forming the As–O–V bands and deactivating the deNO x reaction …”
Section: Introductionmentioning
confidence: 99%
“…However, over the current well-known NH 3 -SCR catalysts, the temperature window of NH 3 -SCR is difficult to match the CB conversion temperature. , Generally, the redox ability of the NH 3 -SCR catalyst is insufficient, which will result in higher CB conversion temperature, low CO 2 selectivity, and more incompletely oxidized products including regenerated PCDD/Fs . Numerous efforts have been focused on VO x -based catalysts recently, especially VO x /TiO 2 -based catalysts are considered as promising candidates for simultaneously eliminating NO x and chlorinated organics. The V 2 O 5 –MoO 3 /TiO 2 catalyst investigated by Huang et al exhibited activity with 100% NO conversion within 200–400 °C and more than 90% CB conversion above 300 °C. However, the N 2 selectivity dramatically decreased above 300 °C.…”
Section: Introductionmentioning
confidence: 99%